Formation of Motivation and Interest to the Study of English at the First Stage of Training - Adam Nazarchuk; Tetyana Zhelikhivska (Pedagogical Discourse, 2012)
The problem of motivation and interest to the study of English at the first stage of training is studied in the article. When teaching the motive is defined as the relation between the student and the whole complex of actions, in the result of which the competence of a certain level is being formed, the aspiration to be engaged of in a certain aspect of activity is woken up in the student